1995
DOI: 10.1016/0269-7491(94)p2609-d
|View full text |Cite
|
Sign up to set email alerts
|

Global climate change: Modelling the potential responses of agro-ecosystems with special reference to crop protection

Abstract: Pests and diseases reduce yields to lower levels than those that could have been potentially obtained, given the restrictions of climate, nutrients and crop varieties. Climatic change not only affects the potential yield levels, but it may also modify the effects of pests and diseases. Modelling can serve as a tool to integrate these processes, ranging from simple removal of plant material to subtle toxic and hormonal effects. Modelling can help to quantify different modes of action such as on photosynthesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 45 publications
0
32
0
2
Order By: Relevance
“…The reason might be attributed to the effects of CO2 con centrations on plants. Since elevated CO2 concentration alters many traits of plants, such as photosynthesis and water use efficiency (Jiang, 1995;Korner, 2000;Wu & Wang, 2000), as well as plant chemical composition (Lin coln et al, 1993;Goudriaan & Zadoks, 1995;Lin, 1998;Wang, 1999). As aphids are phloem feeders, they should show altered responses to the changes in the plant chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…The reason might be attributed to the effects of CO2 con centrations on plants. Since elevated CO2 concentration alters many traits of plants, such as photosynthesis and water use efficiency (Jiang, 1995;Korner, 2000;Wu & Wang, 2000), as well as plant chemical composition (Lin coln et al, 1993;Goudriaan & Zadoks, 1995;Lin, 1998;Wang, 1999). As aphids are phloem feeders, they should show altered responses to the changes in the plant chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…summer and winter crops), crop type (e.g. C3 and C4 plants) or environmental conditions (water and nutrient availability) (Goudriaan and Zadoks 1995;Ainsworth and Long 2005;Thomson et al 2005;Brassard and Singh 2008;Giannakopoulos et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This might result in a parallel northward shift of the distribution of insect pests of xerotherm plant species. By comparing agroecosystem models, Gourdiaan and Zadoks [24] concluded that climatic changes have a great influence on insect pests that follow their host plants. The objective of this study was to gain a deeper knowledge on the trends and pace of dispersion and flight phenology of H. armigera adults in Hungary and to evaluate the influence of weather fronts on the Hungarian distribution of this serious agricultural pest.…”
Section: Introductionmentioning
confidence: 99%